Multi-scale modeling of isobutane alkylation with 2-butene using composite ionic liquids as catalyst. (31st August 2018) - Zheng, Weizhong; Li, Di; Sun, Weizhen; Zhao, Ling
Highlights: CIL-catalyzed isobutane alkylation kinetics was investigated. Kinetic model based on carbonium ion mechanism was established. Alkylation enhancement can be ascribed into the higher solubility and diffusion of isobutane in CIL. Solvation free energy and diffusion coefficient of isobutane in CIL were computed by MD simulation. Abstract: The alkylation kinetics of isobutane with 2-butene catalyzed by composite ionic liquid (CIL) was investigated with batch experiments. The optimized reaction time of CIL-catalyzed alkylation was found to be less than 30 s, much shorter than the traditional H2 SO4 -catalyzed one. Based on the carbonium ion mechanism, the kinetic model was further established, in which the concentration profiles of three groups of key components in alkylates with time can be well predicted, i.e. trimethylpentane (TMPs), dimethylhexanes (DMHs) and heavy ends (HEs). The rate constant related to the formation of TMPs in the CIL alkylation is more than two orders of magnitude larger than that in the H2 SO4 alkylation. The enhancement of the rate constants for the CIL alkylation at the macroscopic scale can be ascribed into the higher solvation and diffusion of isobutane in the CIL at the microscopic scale, which is confirmed by the solvation free energy and diffusion coefficient calculation using molecular dynamics simulation. Hopefully, the multi-scale information in this work can bring novel insights into the understanding of CIL-catalyzed alkylation and further the design and optimization of this process.